Efficacy of mouth rinses and toothpaste on tooth whitening. - Torres, C. R.; Perote, L. C.; Gutierrez, N. C.; Pucci, C. R.; Borges, A. B. (Operative Dentistry, 2013)
People increasingly desire tooth whitening. Considering the wide range of whitening products on the market, this study evaluated the efficacy of whitening toothpastes and mouth rinses compared with the 10% carbamide peroxide (CP) whitening gel. We obtained 120 cylindrical specimens from bovine teeth, which were darkened for 24 hours in a coffee solution. The color measurement was performed by a spectrophotometer using the CIE L*a*b* system, and specimens were divided into six groups according to the use of the following agents: group 1, conventional fluoridated toothpaste; group 2, Close Up White Now; group 3, Listerine Whitening; group 4, Colgate Plax Whitening; group 5, experimental mouth rinse with Plasdone; and group 6, 10% CP Whiteness Perfect. After the simulation of 12 weeks of treatment for groups 1 to 5 and 14 days of treatment for group 6, the specimens were subjected to a new color reading. Data were subjected to one-way analysis of variance (α=0.05), which showed significant differences among groups after 12 weeks for ΔE (p=0.001). Results of the Tukey test revealed that groups 3, 4, and 6 presented significantly higher color alteration than groups 1, 2, and 5. The whitening toothpaste Close Up White Now and the experimental mouth rinse with Plasdone showed similar color alteration as conventional toothpaste after a 12-week treatment simulation. These groups presented significantly lower color alteration compared with whitening mouth rinses Listerine and Colgate Plax Whitening, which showed similar results to those observed after 14 days of bleaching with 10% CP treatment.
Keywords: anticaries agent; detergent; dodecyl sulfate sodium; drug derivative; fluoride; hydrogen peroxide; mouthwash; peroxide; povidone; pyrophosphate; tooth bleaching agent; toothpaste; urea; urea peroxide; animal; cattle; coffee; color; comparative study; dental procedure; drug effect; enamel; instrumentation; materials testing; methodology; pathology; spectrophotometry; time; tooth discoloration; Animals; Cariostatic Agents; Cattle; Coffee; Color; Dental Enamel; Detergents; Diphosphates; Fluorides; Hydrogen Peroxide; Materials Testing; Mouthwashes; Peroxides; Povidone; Sodium Dodecyl Sulfate; Spectrophotometry; Time Factors; Tooth Bleaching; Tooth Bleaching Agents; Tooth Discoloration; Toothpastes; Urea